Spoiler alert : a critical guide - Jaffe, Aaron (Forerunners (Minneapolis, Minn.), 2019)
Concurrent with the compulsory connectivity of the digital age is the rise of the spoiler. The inevitability of information has changed the critical quality of modernity, leaving us with acute vertigo--a feeling that nothing new is left out there. Encompassing memes and trigger warnings, Vilem Flusser and Thomas Pynchon, Spoiler Alert wrangles with the state of surprise in post-historical times. Aaron Jaffe delivers a timely corrective to post-critical modes of reading that demonstrates the dangers of forfeiting critical suspicion.